2022
DOI: 10.1186/s42506-022-00102-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 vaccine hesitancy in patients with mental illness: strategies to overcome barriers—a review

Abstract: Background People with mental health problems are at particular risk both for infection with COVID-19 and for more severe course of illness. Understanding COVID-19 vaccine hesitancy is crucial in promoting vaccine acceptance among people with mental health diagnoses. This review aims to identify the prevalence and discuss factors associated with COVID-19 vaccine hesitancy among the mentally ill population. Main body We conducted a detailed literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 38 publications
(98 reference statements)
2
51
1
3
Order By: Relevance
“…The vaccine hesitancy reported here might be attributed to lack of awareness related to cognitive impairment, lack of motivation and low levels of activity. In a minority of patients, paranoia might be a factor [ 26 , 27 ]. The lower vaccination rate for COVID-19 in individuals with a history of hospitalization for a psychiatric disorder is consistent with the literature regarding other preventive vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine hesitancy reported here might be attributed to lack of awareness related to cognitive impairment, lack of motivation and low levels of activity. In a minority of patients, paranoia might be a factor [ 26 , 27 ]. The lower vaccination rate for COVID-19 in individuals with a history of hospitalization for a psychiatric disorder is consistent with the literature regarding other preventive vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…age, sex, education, annual income) [67][68][69][70] and psychopathological dimensions (e.g. anxiety, panic attacks, agoraphobia, delusions, paranoia, depression) [71]. As previously shown, vaccine uptake in psychiatric patients can be increased by targeted prevention programs [72].…”
Section: Factors Determining Vaccine Uptake In People With Mental Dis...mentioning
confidence: 95%
“…Importantly, several countries have already prioritized vaccination for people with severe mental illness [ 169 , 170 ]. The relationship between COVID-19 vaccination and mental disorders was investigated in several studies [ 171 , 172 , 173 ].…”
Section: Covid-19 Vaccine and Mental Disordersmentioning
confidence: 99%
“…The literature is limited concerning the attitude of people with mental disorders towards vaccination against SARS-CoV-2 [ 172 ]. However, Curtis et al (2022) indicated that lower vaccination coverage was observed among high-risk populations, such as people with severe mental illness [ 179 ].…”
Section: Covid-19 Vaccine and Mental Disordersmentioning
confidence: 99%